Watershed Analysis of the Semenyih River Basin, Selangor, Malaysia - Gasim, Muhammad Barzani (2003)
The Semenyih River Basin has undergone various degrees of land use changes since the last decade, particularly associated with urbanization and industrialization. The total area of the basin is 266.60 km² and contains 36 sub-catchments with sizes ranging from 1.37 to 35.57 km². An integrated study was carried out to determine the various factors of land use changes that may affect the stability of the watershed and its subsequent impacts on water quality. Rock and soil samples were analyzed in a petrographic and XRF methods and sieve analysis for soil. Rainfall-runoff relationships were created to elucidate the hydrologic responses and to develop the graphical analysis. Stream flow pattern of particular years were grouped to show their flow variations. 18 water quality parameters were performed from the 11 sampling locations at the Semenyih River that were also used for the hydrological measurements. The water quality analysis is involved 4 in-situ parameters and 14 laboratory parameters. The relationships of hydrology and water quality variables were determined by regression and correlation analysis. The above three criteria was used together with land use and population density factors to develop the basin classification system.